2016
DOI: 10.1103/physreva.94.063860
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-breaking oscillations in membrane optomechanics

Abstract: We study the classical dynamics of a membrane inside a cavity in the situation where this optomechanical system possesses a reflection symmetry. Symmetry breaking occurs through supercritical and subcritical pitchfork bifurcations of the static fixed point solutions. Both bifurcations can be observed through variation of the laser-cavity detuning, which gives rise to a boomerang-like fixed point pattern with hysteresis. The symmetry-breaking fixed points evolve into self-sustained oscillations when the laser i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…have also been reported. Moreover, complex collective dynamics and synchronization effects have been studied in large optomechanical arrays [36][37][38][39][40] and dimer systems [41][42][43][44][45]. It is worth mentioning that such dynamical features are also common to configurations where a cavity field is coupled to another optical field either in a master-slave [46][47][48] or in a mutual [49,50] fashion.…”
Section: Introductionmentioning
confidence: 99%
“…have also been reported. Moreover, complex collective dynamics and synchronization effects have been studied in large optomechanical arrays [36][37][38][39][40] and dimer systems [41][42][43][44][45]. It is worth mentioning that such dynamical features are also common to configurations where a cavity field is coupled to another optical field either in a master-slave [46][47][48] or in a mutual [49,50] fashion.…”
Section: Introductionmentioning
confidence: 99%
“…Classical nonlinear optomechanics is relevant in the case of highly populated optical and mechanical modes. Though it attracted slightly less attention during the initial evolution of modern cavity optomechanics, a number of significant theoretical studies have been devoted to understanding the structure of the phase space, including limit cycles and multistability [22][23][24][25][26], and chaotic dynamics [27,28]. Experimental studies have been relatively rare, but important phenomena have already been observed, including limit cycles [29,30], period doubling and chaos [31][32][33][34][35][36], the predicted multistable attractor diagram [37,38] which is characteristic for optomechanical systems, as well as further aspects [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Chaos and non-linear behaviour have been studied in a wide variety of areas with numerous applications, in particular, in the functioning of random number generators [72] and in encrypted communications [73][74][75]. In OM systems, there have been numerous reports detailing the emergence of chaos in both standard and hybrid systems through theoretical and experimental means [32,[76][77][78][79][80][81][82]. The key objective to achieve, while studying such systems, is to be able to manipulate/control the random behaviour for potential applications and some of the above cited studies have attempted to address this question.Occurrence of chaos in typical OM systems necessitates the use of large pump powers which is not feasible for such systems consisting of nanomechanical mirrors.…”
Section: Introductionmentioning
confidence: 99%